2016
DOI: 10.1021/acs.analchem.5b04591
|View full text |Cite
|
Sign up to set email alerts
|

Specific Noncompetitive Immunoassay for HT-2 Mycotoxin Detection

Abstract: Here we demonstrate a novel homogeneous one-step immunoassay, utilizing a pair of recombinant antibody antigen-binding fragments (Fab), that is specific for HT-2 toxin and has a positive readout. Advantages over the conventional competitive immunoassay formats such as enzyme-linked immunosorbent assay (ELISA) are the specificity, speed, and simplicity of the assay. Recombinant antibody HT2-10 Fab recognizing both HT-2 and T-2 toxins was developed from a phage display antibody library containing 6 × 10(7) diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 35 publications
3
56
1
Order By: Relevance
“…The authors concluded that the DON http://www.wageningenacademic.com/doi/pdf/10.3920/WMJ2016.2138 -Friday, May 11, 2018 11:37:55 PM -IP Address:18.236.120.13 concentrations quantitated by LC-MS/MS correlated nicely with those obtained by the Quenchbody method (r 2 =0.98). The group of Arola et al (2016) demonstrated a novel rapid one-step immunoassay for determination of HT-2, utilising a pair of recombinant antibody antigen-binding fragments (Fab). The primary Fab recognises HT-2 and the secondary Fab binds specifically to the immune complex formed by the primary antibody and HT-2.…”
Section: Trichothecenesmentioning
confidence: 99%
“…The authors concluded that the DON http://www.wageningenacademic.com/doi/pdf/10.3920/WMJ2016.2138 -Friday, May 11, 2018 11:37:55 PM -IP Address:18.236.120.13 concentrations quantitated by LC-MS/MS correlated nicely with those obtained by the Quenchbody method (r 2 =0.98). The group of Arola et al (2016) demonstrated a novel rapid one-step immunoassay for determination of HT-2, utilising a pair of recombinant antibody antigen-binding fragments (Fab). The primary Fab recognises HT-2 and the secondary Fab binds specifically to the immune complex formed by the primary antibody and HT-2.…”
Section: Trichothecenesmentioning
confidence: 99%
“…The group of Arola et al (2016) demonstrated a novel rapid one-step immunoassay for determination of HT-2, utilising a pair of recombinant antibody antigen-binding fragments (Fab). The primary Fab recognises HT-2 and the secondary Fab binds specifically to the immune complex formed by the primary antibody and HT-2.…”
Section: Trichothecenesmentioning
confidence: 99%
“…The authors concluded that the DON concentrations quantitated by LC-MS/MS correlated nicely with those obtained by the Quenchbody method (r 2 =0.98). The group of Arola et al (2016) demonstrated a novel rapid one-step immunoassay for determination of HT-2, utilising a pair of recombinant antibody antigen-binding fragments (Fab). The primary Fab recognises HT-2 and the secondary Fab binds specifically to the immune complex formed by the primary antibody and HT-2.…”
Section: Trichothecenesmentioning
confidence: 99%